1970
DOI: 10.1139/b70-163
|View full text |Cite
|
Sign up to set email alerts
|

Separation of noncharged carbohydrates from plant material by gas–liquid chromatography of their trimethylsilyl derivatives

Abstract: A technique is described for the quantitative separation of very low concentrations of carbohydrates by gas–liquid chromatography using polar and nonpolar silicone liquid phases and TMS (trimethylsilyl) derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1973
1973
1981
1981

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Evidence from gas chromatographic analysis shows that the exudates contain four sugars including pentoses, the preferred carbon sources for induction of nitrogenase activity (BERGERSEN and GIBSON 1978). Similar studies have revealed that these substances are major constituents of legume root exudates (SHAY and HALE 1973, HAMLEN et al 1970). Evidence from this study is contrary to the conclusion drawn from a plant tissue culture study that the plant cell is capable of supplying the tricarboxylic acid but not pentose sugar (CHILD and KURTZ 1978).…”
Section: Discussionsupporting
confidence: 56%
“…Evidence from gas chromatographic analysis shows that the exudates contain four sugars including pentoses, the preferred carbon sources for induction of nitrogenase activity (BERGERSEN and GIBSON 1978). Similar studies have revealed that these substances are major constituents of legume root exudates (SHAY and HALE 1973, HAMLEN et al 1970). Evidence from this study is contrary to the conclusion drawn from a plant tissue culture study that the plant cell is capable of supplying the tricarboxylic acid but not pentose sugar (CHILD and KURTZ 1978).…”
Section: Discussionsupporting
confidence: 56%
“…The supernatant containing the dissolved sugars was evaporated to dryness. Trimethylsilyl derivatives of the sugars were made by dissolving them in 1.0 ml of pyridine followed by the addition of 0.9 ml of hexamethyldisilazane and 0.1 ml of trifluoroacetic acid (1,6,15,17). Since exudates were recovered from Hoagland's solution, the recovery of a mixture of standard sugars from 3 liters of Hoagland's solution was used to determine the quantitative efficiency of the technique used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…6). In other plants the presence of sorbitol and mannitol may indicate diseased condition (Hamlen, Lukezic & Bloom, 1970) and both may be identified with 5% OV-1 as liquid phase on 60j80 mesh chromosorb. Cereals are of particular interest to the brewing industry and glc has been applied to the determination of sugars in distilled spirits (Martin & Eib, 1968) and in wort (Otter, 1967).…”
Section: Applications To Foodmentioning
confidence: 99%